Órteses, Próteses e Meios auxiliares de locomoção (OPM) nas oficinas ortopédicas da rede de cuidados à pessoa com deficiência - Lima, Maria Letícia de Melo (2021)
Introduction: Access in a timely and qualified manner to Orthotics, Prostheses and Auxiliary Means of Locomotion (OPM) positively reflects on the resolution and quality of rehabilitation actions. Thus, it is seen that the use of Assistive Technology (TA) has a great impact on functionality related to the execution of activities and involvement in situations of social participation of people who experience living with physical disabilities and reduced mobility. In order to make it possible to enable comprehensive care, it is essential that there be the construction of health care points for people who would benefit from timely access to OPM in Brazil. Objective: To analyze the supply of dispensing of OPM assistive devices by Orthopedic Workshop in Brazil in 2019 that have the financial incentive of the Federal Government by the modality of Monthly Costing. Methodological Considerations: This is an exploratory and descriptive study of secondary data, with a quantitative approach. Orthopedic Workshops are present in all regions of the country, totaling thirty-two health facilities (32), according to the inclusion and exclusion criteria of the research. The secondary data were extracted from the Outpatient Information System of the Informatics Department of the Unified Health System (SIASUS - DATASUS) in the period from March to June 2020 and, after the delimitation of the sample design of Installed Capacity of Orthopedic Workshops of the SUS, the values practiced by SUS in the Management System of the Table of Procedures were researched, Medicines and OPM in SUS (SIGTAP). In view of the object of study of this research, after data filtration, a new categorization of the variables was performed for optimization in the statistical analysis and better discussion about them. At the end, from the new categorization, the dispensing outcomes of the products of: Lower Limb Prostheses were defined; Upper limb prostheses; Lower limb orthotics; Upper limb orthotics; Auxiliary means of locomotion and other orthosis (covering Other auxiliary media, Wheelchair and Other footwear and insoles); Repair and adaptation of OPM (covering adaptation and maintenance of OPM and repair of lower limb prosthesis) and Other prosthesis. The data were processed by statistical analysis using the Value Index Calculation and Cluster Analysis, performed in the Statistical Package for the Social Sciences (SPSS), version 20. Results: Among the 32 Orthopedic Workshops, most are in the Southeast region, with a total of 13 Workshops. With regard to the level of management, the majority has a level of municipal management (22), being only 10 with state management level. Regarding the products and procedures performed by the Workshops, the Auxiliary Means of Locomotion and Orthotics stand out with the highest dispensation, offering annually a total of 75,817 products. Next we have the Repair and Adaptation of OPM, with 32,726 services provided and thirdly, the dispensation of Lower Limb Orthosis, with 20,228 products. From the Value Index Calculation, an unpredictability was observed in the process of resource acquisition, production and dispensation of OPM. Thus, it is predicted that there is no regularity in the supply of dispensation during all months of the year. The Cluster Analysis corroborates the descriptive data, highlighting once again the majority impact of dispensing the Auxiliary Means of Locomotion and Orthotics. In addition, the Cluster Analysis demonstrates discrepancy between the twelve months of 2019, indicating once again the inconstancy in the opm supply process, as well as in the schedule of receiving resources and production. Conclusion: Orthopedic Workshops were mapping, as well as the characterization of the products and services offered by the SUS Workshops in 2019. The analysis of the budgetary impact involved in the supply of OPM at the Federal level demonstrated irregularity in the process, presenting unpredictability of this dispensing process. These findings will support further studies and health decision-making by management regarding the expansion and qualification of the supply of non-surgical OPM in Brazil.